2013
DOI: 10.1016/j.psyneuen.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in pre-carcinogen cytokine and corticosterone concentrations and depressive-like behavior predict tumor onset in rats exposed to a carcinogen

Abstract: Summary Individual variation in the susceptibility to chronic disease can be attributed to both genetic and environmental factors. Measures of the immune, nervous, and endocrine systems are predictive of survival outcomes after a chronic disease is diagnosed. However, determining biomarkers or “traits” that predict risk before chronic disease development remains elusive. In this study, natural individual variation in circulating cytokines, corticosterone, and depressive-like behaviors (using the Porsolt forced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…In our initial hypothesis, the predictive value of the corticosterone concentrations for chemical carcinogenesis should be similar to norepinephrine's. Recently, Pyter and Prendergast (2013) found that increased plasma corticosterone levels prior to carcinogen treatment predicted mammary cancer onset, but the authors did not evaluate the hormone tissue levels in the microenvironment. However, some evidences can support the negative predictive effect of glucocorticoid for carcinogenesis.…”
Section: Tablementioning
confidence: 99%
“…In our initial hypothesis, the predictive value of the corticosterone concentrations for chemical carcinogenesis should be similar to norepinephrine's. Recently, Pyter and Prendergast (2013) found that increased plasma corticosterone levels prior to carcinogen treatment predicted mammary cancer onset, but the authors did not evaluate the hormone tissue levels in the microenvironment. However, some evidences can support the negative predictive effect of glucocorticoid for carcinogenesis.…”
Section: Tablementioning
confidence: 99%